DAMPAK IKLIM ORGANISASI TERHADAP KEPUASAN KERJA (Studi pada Karyawan Tetap di Polman Bandung) - Ariyani, Emma Dwi (Program Studi Pendidikan Manajemen Perkantoran, 2012)
The purpose of this research is to prove that employee’s perception of organizational climate caninfluence employee’s job satisfaction. The research was conducted on 100 permanent employees inPolman Bandung who has worked at least 5 years. Data analysis using path analysis to see how muchinfluence the independent variable that is organizational climate on dependent variable that is jobsatisfaction. The results showed that the influence of organizational climate on job satisfactionamounted 41,6%. The findings in this research strengthen other researches that shows that theorganizational climate affect the job satisfaction.